Несимметрия параметров электрических сетей 750 кВ ОЭС Украины в неполнореакторных режимах - Веприк, Ю.Н.; Линник, Е.Н. (Електротехніка і електромеханіка, 2012)
The paper presents a phase coordinate equation based mathematical
model of an electrical network that allows reproducing
single-ended modes under single or multiple asymmetry in the
network. Studies of the complex unbalance in 750 kV electric
networks in the Ukrainian united power grid are made, the unbalance
resulted from open-phase switching of shunt reactors
groups.